O cristianismo como religião da décadence e contrária aos impulsos vitais em O Anticristo, de Nietzsche - Marco Junio Abade (2010)
This dissertation is about the conception of Christianism as a manifestation of a physiological fact called Décadence, as a explained by Nietzsche in The Antichrist. Christianism is understood as a symptom of a process of physiological destructuring, whose ideals operate as an instrument of conservation and further vital corruption. Moreover, it is considered the philosopher's task of reassembling the Christianism religious phenomenon to their origin conditions (Jewish ground) and distinguishing it from Church Christianism - whose founder is the Apostle Paul- and Autentic Christianism - taught and lived by Jesus of Nazareth -, whose physiological typology is analyzed. A paradigmatic case of degeneration of vital instinct, Christianism is understood as the substrate of values of western civilization, in special the modern one.